Social Exclusion and Poverty in Rural Areas of Britain - Mark Shucksmith (Belgeo)
This paper discusses the ways in which economic, social and political forces for change operate in rural areas to produce social exclusion for some people and social groups. After a brief review of these forces for change, as they operate across Europe, the paper turns to consider the meaning of the term ”social exclusion” and how the experiences of individuals and social groups might be related to such forces. Following this, the paper draws on a number of recent empirical studies to illustrate how social exclusion operates in rural areas of Britain. The paper draws attention to the effects on sustainable livelihoods of the ascendancy of market processes, and the waning of state systems, as a result of the neo-liberal hegemony which has hastened deregulation, privatisation, reductions in public expenditure and global capital’s penetration of labour and product markets.